The Contribution of Indonesia's Ethnographic-Based Accounting Research Trends (2013-2022): An Analysis Study Using The Bibliometrics - Saputra, Irwan Adimas Ganda; Hakim, Luqman; Pamungkas, Heni Purwa (Jurnal Pendidikan Akuntansi (JPAK), 2024)
This research aims to analyse Indonesia's trends and contributions in ethnographic research through a bibliometric study using the Scopus database from 2013-2022. This research is a type of qualitative research using bibliometric analysis methods. data collection and analysis techniques are carried out in five stages starting with searching for data using certain desired keywords and ending with analysed data. The conclusion obtained from the results of this study is that ethnographic publications increase from year to year. The United States has contributed the most in the last decade, while Indonesia is in fourth place. Universitas Airlangga, Universitas Padjajaran, and Universitas Gadjah Mada are the three Indonesian institutions that contribute to ethnographic research. The analysis also found six clusters in the visualisation of ethnographic research trends, consisting of four main clusters and two secondary clusters. The results of the study have implications and contributions to help researchers to analyse ethnographic research trends globally and provide an overview and recommendations for future research directions. This research provides an overview of the development of ethnographic research in accounting and provides an overview of the novelty of similar research.